KEBIJAKAN INDONESIA DALAM MENGHADAPI PENURUNAN EKSPOR BATUBARA KE INDIA AKIBAT PANDEMI COVID-19 SELAMA TAHUN 2020 - Nur Amaliya; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to explain about Indonesia’s policy during 2020 after seeing the fact that its coal exports to India decrease dramatically due to the COVID-19 pandemic. In fact, India is one of Indonesia's main export destinations after China.The research method used in this research is descriptive analysis with qualitative research type. The data collection technique used is 'library research', which is a systematic procedure for reviewing and evaluating both printed and electronic documents. This study uses the theory of international cooperation as an analytical tool to explain Indonesia’s policies.This study shows that Indonesia took two important policies in response to the decline in coal exports to India. First, Indonesia chooses to reduce the volume of domestic production in order to suppress global coal prices from getting weaker which will harm exporting countries. Second, Indonesia is increasing its cooperation with India through a bilateral communication forum, namely the 'joint working group'. Keyword: Indonesia’s policy, Decrease Coal Export, COVID-19